P222 A retrospective study of disease recurrence post thoracotomy for non-small cell lung cancer. (16th November 2010) - Naqvi, J; Navani, N; Saeed, S; Shastry, M; Groves, A; Shaw, P; Lawrence, D; Kolvekar, S; Hayward, M; Janes, S
Abstract : Background: Surgery is the treatment of choice for early stage non-small cell lung cancer (NSCLC). However, curative intent is commonly not achieved due to inaccurate clinical staging and disease recurrence. Aim: We aimed to determine the incidence of futile thoracotomies (FT) in patients with NSCLC following surgery with curative intent. In addition, we wished to identify prognostic factors that predicted FT. Methods: In this analytical retrospective cohort study, thoracotomy cases between October 2003 and September 2008 at a single institution were identified. Confirmed cases of primary NSCLC only were included. A thoracotomy was deemed futile if any one of the following criteria were met: pathologically confirmed N2, N3, or M1 disease, an exploratory thoracotomy, or a thoracotomy in a patient who developed recurrent disease or died within 1 year of surgery. When a PET scan was performed, the SUVmax of the primary tumour was reported by a radiologist blinded to the clinical information. Case notes and hospital systems were interrogated for evidence of recurrence and survival. Statistical analysis was performed with STATA version 10 for Windows. Results: We identified 171 consecutive patients with NSCLC who underwent lung resection with curative intent. 105 (61%) were male and mean age at the time of surgery was 66 years. 134 (78%) had lobectomy, 8 bi-lobectomy, 19 pneumonectomy and 10 sub-lobar resection (segmentectomy or wedge resection). Overall 46 (27%) underwent FT. Nine patients (5.2%) had clinically unsuspected N2 disease at pathological staging. An SUVmax of the primary tumour greater than 8 was associated with an increased risk of FT (RR 2.35 (p=0.03)) (Abstract P222 Table 1 ). The presence of lymphovascular invasion was also associated with a increased risk of FT (RR 1.71 (p=0.04)). Those with a primary tumour greater than or equal to 3 cm in size had a RR of 1.91 (p=0.02) of FT. Conclusions: Between 2003 and 2008, 27% of patients at our cardiothoracic centre for lung cancer underwent a futile thoracotomy. High SUVmax, the presence of lymphovascular invasion and tumour size ≥3 cm are predictors of FT. Future, prospective studies employing adjuvant chemotherapy in these patient groups are warranted.